Age of platelet concentrates and time to the next transfusion. Issue 1 (31st October 2017) - Caram‐Deelder, Camila; van der Bom, Johanna G.; Putter, Hein; Leyte, Anja; Kerkhof, Daan van de; Evers, Dorothea; Beckers, Erik A.; Weerkamp, Floor; Hudig, Francisca; Zwaginga, Jaap Jan; Rondeel, Jan M.M.; de Vooght, Karen M.K.; et al.
Abstract : BACKGROUND: Storage time of platelet (PLT) concentrates has been negatively associated with clinical efficacy outcomes. The aim of this study was to quantify the association between storage time of PLT concentrates and interval to the next PLT transfusion for different types of PLT components, stored for up to 7 days and transfused to transfusion‐dependent hematooncology patients with thrombocytopenia. STUDY DESIGN AND METHODS: From a cohort of patients from 10 major Dutch hospitals, patients were selected whose transfusion patterns were compatible with PLT transfusion dependency due to hematooncologic disease. Mean time to the next transfusion and mean differences in time to the next transfusion for different storage time categories (i.e., fresh, <4 days; intermediate, 4‐5 days; and old, >5 days) were estimated, per component type, using multilevel mixed‐effects linear models. RESULTS: Among a cohort of 29, 761 patients who received 140, 896 PLT transfusions we selected 4441 hematooncology patients who had received 12, 724 PLT transfusions during periods of PLT transfusion dependency. Transfusion of fresh, compared to old, buffy coat–derived PLTs in plasma was associated with a delay to the next transfusion of 6.2 hours (95% confidence interval [CI], 4.5‐8.0 hr). For buffy coat–derived PLTs in PAS‐B and ‐C this difference was 7.7 hours (95% CI, 2.2‐13.3 hr) and 3.9 hours (95% CI, –2.1 to 9.9 hr) while for apheresis PLTs in plasma it was only 1.8 hours (95% CI, –3.5 to 7.1 hr). CONCLUSION: Our results indicate that the time to the next transfusion shortens with increasing age of transfused buffy coat–derived PLT concentrates. This association was not observed for apheresis PLTs.